Systematic review on fecal calprotectin in cystic fibrosis - Eduarda Sampaio Lazzarotto; Jannaina Ferreira de Melo Vasco; Fabiane Führ; Carlos Antônio Riedi; Nelson Augusto Rosário Filho (Elsevier, 2023)
Objectives: Fecal calprotectin is an inflammatory marker used for monitoring intestinal diseases. It has been studied as a marker of intestinal inflammation in cystic fibrosis (CF), a multi-systemic genetic disease caused by alterations to the CFTR gene. Manifestations of the disease favor a systemic inflammation not limited to the respiratory tract, therefore, calprotectin is a non-invasive and effective diagnostic method. The aim of the study was to perform a systematic review of the literature with a qualitative synthesis of studies. Sources: The articles were selected from PubMed, Web of Science, Scielo and Lilacs. Summary of the findings: Nine studies were selected for that qualitative synthesis, one was a randomized clinical trial, and eight were case-control or cohort designs. Most studies have indicated that calprotectin is a marker of systemic inflammation in CF and not just intestinal inflammation. Calprotectin is an aid in monitoring inflammatory bowel conditions in patients with cystic fibrosis. Conclusion: Further studies should be conducted to investigate the role of this marker in the systemic inflammation of CF.